2018
DOI: 10.1007/s00428-018-2305-5
|View full text |Cite
|
Sign up to set email alerts
|

The landscape of genetic alterations in ameloblastomas relates to clinical features

Abstract: Ameloblastoma is a mostly benign, but locally invasive odontogenic tumor eliciting frequent relapses and significant morbidity. Recently, mutually exclusive mutations in BRAF and SMO were identified causing constitutive activation of MAPK and hedgehog signaling pathways. To explore further such clinically relevant genotype-phenotype correlations, we here comprehensively analyzed a large series of ameloblastomas (98 paraffin block of 76 patients) with respect to genomic alterations, clinical presentation, and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
107
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(117 citation statements)
references
References 18 publications
6
107
1
3
Order By: Relevance
“…One possible explanation for this relatively high prevalence of BRAF V600E mutations is racial and genetic differences. In a study of genetic alterations in ameloblastoma, multiple gene mutations are more frequently found in German and French patients than Turkish ones, suggesting that genetic background may influence mutational spectra . Moreover, conflicting results regarding BRAF V600E frequency have been presented in odontogenic keratocyst (OKC).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation for this relatively high prevalence of BRAF V600E mutations is racial and genetic differences. In a study of genetic alterations in ameloblastoma, multiple gene mutations are more frequently found in German and French patients than Turkish ones, suggesting that genetic background may influence mutational spectra . Moreover, conflicting results regarding BRAF V600E frequency have been presented in odontogenic keratocyst (OKC).…”
Section: Discussionmentioning
confidence: 99%
“…Second, other EMT‐TFs such as ZEB families are involved in tumorigenesis of ameloblastoma in association with BRAF V600E. Last, material types may affect the results of correlation analysis, considering that contrasting conclusions about the relationship between BRAF V600E and EMT have been drawn in melanoma and PTC depending on whether cell lines or tissue samples were used . Further investigations are needed to test these hypotheses and to clarify the biological role of BRAF V600E and EMT in ameloblastoma and other tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced next generation sequencing (NGS) analyses identified the high frequency of BRAF V600E and SMO L412F mutations in ameloblastoma . In 2018, Gültekin et al reported novel somatic mutation of oncogenes and tumor suppressor genes in addition to BRAF and SMO mutations .…”
Section: Introductionmentioning
confidence: 99%
“…Advanced next generation sequencing (NGS) analyses identified the high frequency of BRAF V600E and SMO L412F mutations in ameloblastoma . In 2018, Gültekin et al reported novel somatic mutation of oncogenes and tumor suppressor genes in addition to BRAF and SMO mutations . Using cell culture model with established ameloblastoma cell lines, Nakao et al reported that fibroblast growth factor (FGF) −7 and −10 stimulates ameloblastoma proliferation .…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that 46% to 82% of solid/multicystic ameloblastomas harbors BRAF V600E mutation (Brown et al, ; Guan et al, ; Kurppa et al, ; Sweeney et al, ), while UAM demonstrated higher BRAF V600E mutation frequency (63%–94%) (Heikinheimo et al, ; Pereira et al, ). More recent studies revealed that less common cell types of ameloblastoma showed different rates of BRAF V600E mutation: acanthomatous (44%, 7/16), granular (50%, 2/4), and basaloid (33%, 2/6) (Gultekin et al, ; You et al, ). However, ameloblastoma with mucous cell differentiation still has no particular BRAF V600E up to date mutation data.…”
Section: Introductionmentioning
confidence: 99%